2015
DOI: 10.1080/15257770.2015.1078470
|View full text |Cite
|
Sign up to set email alerts
|

Purine and Guanine Thioglycoside Analogs: Novel Synthesis of a New Class of Pyrazolo[1,5-a][1,3,5]Triazine-4-Thioglycoside Derivatives under Microwave Activation

Abstract: A first microwave-assisted synthesis of a new class of novel purine thioglycoside analogues from readily available starting materials has been described. The key step of this protocol is the formation of sodium pyrazolo[1,5-a][1,3,5]triazine-4-thiolates via condensation of 5-amino-1H-pyrazoles with sodium cyanocarbonimidodithioate salt under microwave irradiation, followed by coupling with halo sugars to give the corresponding purine thioglycoside analogues. Further studies on the application of this method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 16 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Nucleoside analogue inhibitors, currently used to treat viral infections, are chemically synthesized analogues of purines and pyrimidines in which the sugar moiety or heterocyclic ring has been altered. Nucleoside analogues are managed as prodrugs, which are metabolized by host or viral kinases to their active triphosphate once inside the cell. Nucleoside analogues exert inhibitory effects on viral replication by one or more mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleoside analogue inhibitors, currently used to treat viral infections, are chemically synthesized analogues of purines and pyrimidines in which the sugar moiety or heterocyclic ring has been altered. Nucleoside analogues are managed as prodrugs, which are metabolized by host or viral kinases to their active triphosphate once inside the cell. Nucleoside analogues exert inhibitory effects on viral replication by one or more mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic compounds containing pyrazole rings are also efficacious components in many multi-component syntheses (Tu et al, 2014); we have reported and reviewed their use as novel synthetic intermediates Abu-Zaied et al, 2018Metwally et al, 2024). We have also synthesized various pyrazole-fused heterocyclic compounds as bioactive agents acting as antimetabolites (Elgemeie & Abu-Zaied, 2015;Elgemeie et al 2017aElgemeie et al ,b, 2019Mohamed-Ezzat & Elgemeie, 2023).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The reaction proceeded smoothly with microwave‐assisted protocol optimized with mild acidic medium (acetic acid) without observation of any side products (Scheme 21). The product 53 was further engaged in coupling with sugars to prepare purine thioglycosides [30a] …”
Section: Microwave‐assisted Chemistry Of Poly‐aza‐heterocyclesmentioning
confidence: 99%